Justice matters : legacies of the Holocaust and World War II - Weissmark, Mona Sue (Oxford Univ. Press, 2004)
"In the fall of 1992, in a small room in Boston, MA, an extraordinary meeting took place. For the first time, the sons and daughters of Holocaust victims met face-to-face with the children of Nazis for a fascinating research project to discuss the intersections of their pasts and the painful legacies that history has imposed on them." "Central to the perspectives of each group, Weissmark found, were stories, searing anecdotes passed from parent to grandchild, from aunt to nephew, which personalized with singular intensity the experience. She describes how these stories or "legacies" transmit moral values, beliefs, and emotions and thus freeze the past into place. For instance, most children of Nazis reported that their parents told them stories about the war, whereas children of survivors reported that their parents told them stories about the Holocaust. The daughter of a survivor said, "I didn't even know there was a war until I was a teenager. I didn't even know fifty million people were killed during the war. I thought just six million Jews were killed." The daughter of a Nazi officer recalled, "I didn't know about the concentration camps until I was in my teens. First I heard about the [Nazi] party. Then I heard stories about the war, about bombs falling or about not having food."" "At a time when the political arena is saturated with talk of justice tribunals, reparations, and revenge management, Justice Matters provides valuable insights into the aftermath of ethnic and religious conflicts around the world, from Rwanda to the Balkans, from Northern Ireland to the Middle East. The stories recounted here, and the lessons they offer, have universal applications for any divided society determined not to let the ghosts of the past determine the future."--BOOK JACKET.